ANALYSING THE RELATIONSHIP BETWEEN MONEY MANAGEMENT AND SOCIAL INTERACTION OF THE HIGHER SECONDARY SCHOOL BOYS - Qayoum, Abdul (IJRDO - Journal of Social Science and Humanities Research, 2019)
ABSTRACTDiscipline is one of the most effective factors in learning process. In the modern educational plans, the main purpose of discipline is to create the educational environment and opportunities for learning process. Indeed, discipline is an instrument for realizing the high educational goals that leads to the students’ growth and progress in every dimension. In order to this, the student will acquire a level of self-discipline and self-control. The main objective of this study is to examine the significant relationship between money management and social interaction factors of self discipline. It basically used the descriptive research design in carrying out the study and in selecting the respondents, random sampling were undertaken to 63 students in Government Higher Secondary school Handwara in rural District Kupwara of Jammu & Kashmir state, India. The structured questionnaires were used to gather the information Data were analyzed using statistical tools such as frequencies, percentages, mean, standard deviation, regression and correlation. Findings of the study revealed that 100% were boys under the age group of 16 years. Majority of boy’s father’s occupation was employee and 84.1 per cent of the mother’s functioning as house wife/home maker. Mean responses of money management and social interaction showed that there was no significant difference between money management and social interaction of the students. Money management and social interaction showed a positive no significant correlation at 1% level. Both self discipline factors have an impact on students’ discipline behavior at school with 0.001 where the results were not statistically significant 1% level. This may be due to money management and social interactions among the students, whom cannot able to manage the money spending for their personnel factors and cannot, have social assessment between family and friends. This can be interpreted that as the money management and social interaction factors were related together for a student’s activity at school and home. Interestingly, the studying hours which are used to be a predictor of students’ academic performance is found to have no relationship to academic performance that can also be interpreted that, regardless of whether the student spent short or long time with their studies, the results might be the same.